2019
DOI: 10.3390/medicina56010006
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for the Relief of Chronic Pain: A Synthesis of Systematic Reviews

Abstract: Background and Objectives: It is estimated that 28 million people in the UK live with chronic pain. A biopsychosocial approach to chronic pain is recommended which combines pharmacological interventions with behavioural and non-pharmacological treatments. Acupuncture represents one of a number of non-pharmacological interventions for pain. In the current climate of difficult commissioning decisions and constantly changing national guidance, the quest for strong supporting evidence has never been more important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 209 publications
(122 reference statements)
0
22
0
2
Order By: Relevance
“…Evidence-Based Complementary and Alternative Medicine nausea and vomiting than analgesic drug treatment alone. Acupuncture treatment for cancer pain is considered to have sufficient evidence to determine its effectiveness [37]; these results are encouraging and support further research on acupuncture treatment for cancer.…”
Section: Discussionmentioning
confidence: 89%
“…Evidence-Based Complementary and Alternative Medicine nausea and vomiting than analgesic drug treatment alone. Acupuncture treatment for cancer pain is considered to have sufficient evidence to determine its effectiveness [37]; these results are encouraging and support further research on acupuncture treatment for cancer.…”
Section: Discussionmentioning
confidence: 89%
“…One review presented 'the challenge of adequacy of dose' recently. 33 Our group built a scoring Open access instrument to calculate the dose of acupuncture from four parameters. 53 Based on the sum of the scores, we defined three doses of acupuncture treatment: high dosage, medium dosage and low dosage.…”
Section: Discussionmentioning
confidence: 99%
“…32 In 2019, however, a review suggested that acupuncture provided relief of pain associated with KOA. 33 Most meta-analyses mainly focused on chronic pain and peripheral joint OA and were not specific to KOA. 16 17 34-37 Although there were some systematic reviews conducted to establish the association of acupuncture with KOA, few drew a definitive conclusion.…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…There is some evidence that acupuncture may be beneficial in the treatment of neurological pain (12). Additionally, acupuncture is known to be a safe treatment with few adverse reactions (13). The curative effect of acupuncture in the treatment of this disease is certain.…”
Section: Introductionmentioning
confidence: 99%